Prion protein-specific antibodies that detect multiple TSE agents with high sensitivity. - Sandra McCutcheon; Jan P M Langeveld; Boon Chin Tan; Andrew C Gill; Christopher de Wolf; Stuart Martin; Lorenzo Gonzalez; James Alibhai; A Richard Alejo Blanco; Lauren Campbell; Nora Hunter; E Fiona Houston (PLoS ONE)
This paper describes the generation, characterisation and potential applications of a panel of novel anti-prion protein monoclonal antibodies (mAbs). The mAbs were generated by immunising PRNP null mice, using a variety of regimes, with a truncated form of recombinant ovine prion protein spanning residues 94-233. Epitopes of specific antibodies were mapped using solid-phase Pepscan analysis and clustered to four distinct regions within the PrP molecule. We have demonstrated the utility of these antibodies by use of Western blotting and immunohistochemistry in tissues from a range of different species affected by transmissible spongiform encephalopathy (TSE). In comparative tests against extensively-used and widely-published, commercially available antibodies, similar or improved results can be obtained using these new mAbs, specifically in terms of sensitivity of detection. Since many of these antibodies recognise native PrPC, they could also be applied to a broad range of immunoassays such as flow cytometry, DELFIA analysis or immunoprecipitation. We are using these reagents to increase our understanding of TSE pathogenesis and for use in potential diagnostic screening assays.